1986
DOI: 10.1136/thx.41.4.311
|View full text |Cite
|
Sign up to set email alerts
|

Postal survey of bronchoscopic practice by physicians in the United Kingdom.

Abstract: In 1983 a postal survey of the bronchoscopic practice of chest physicians in the United Kingdom produced a 90% response rate. Two hundred and thirty one physicians were carrying out bronchoscopy; they had performed about 40 000 bronchoscopies in the preceding year, 87% of these being fibreoptic procedures with topical anaesthesia. The mortality rate of fibreoptic bronchoscopy was 0.04%, with a 0.12% incidence of major complications. Transbronchial biopsy carried both an appreciably higher mortality rate of 0.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
91
4
13

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(119 citation statements)
references
References 27 publications
11
91
4
13
Order By: Relevance
“…9 With the inclusion of TBB these rates rise to 0.12% and 2.7%, respectively. However, when looking at the high-risk immunosuppressed oncology population the complication rate rises to between 5% and 15% 8,10 with the much higher complication rates in those having TBB due mainly to bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…9 With the inclusion of TBB these rates rise to 0.12% and 2.7%, respectively. However, when looking at the high-risk immunosuppressed oncology population the complication rate rises to between 5% and 15% 8,10 with the much higher complication rates in those having TBB due mainly to bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…1,24 In addition, some patients with NSCLC will have contraindications to endobronchial biopsy. 25 The management of advanced NSCLC remains an issue of great importance. The results from a national survey of patients with NSCLC in the United States demonstrated that 67.2% of patients had stage III/IV disease, and [33% of patients with NSCLC received multimodality treatment, which consisted most commonly of chemotherapy and radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…First, fibreoptic bronchoscopy became more widely available (Simpson et al, 1986), and second, chemotherapy was established as first-line treatment for patients with small cell lung cancer (MRC Lung Cancer Working Party, 1979).…”
mentioning
confidence: 99%